Ophthalmological manifestations in ichthyosis: from eyelid involvement to corneal complications - Manal Chnaoui,; M. Sidki,; M.R. Bentouhami,; Y. Hidane,; A. Mchachi,; L. Benhmidoune,; R. Rachid, (Public Health, 2026)
Ichthyosis is a rare disorder of keratinization with frequent but underrecognized ocular involvement. Eyelid abnormalities and ocular-surface disease may lead to severe corneal complications, especially in congenital forms. Objective: To describe ophthalmological manifestations in patients with ichthyosis and to identify factors associated with corneal complications. Methods: Retrospective observational analytical study of eight patients with clinically confirmed ichthyosis seen in an ophthalmology consultation. Data included demographics, ichthyosis type, eyelid examination, slit-lamp findings, dry-eye assessment, treatments, and outcomes. Results are presented as counts and percentages; associations between eyelid abnormalities and corneal involvement were explored descriptively. Results: Mean age was 12.5 years (range 6 months–32 years); five patients (62.5%) were male. Severe congenital forms represented 62.5% of cases. Eyelid involve- ment occurred in 6/8 patients (75%): lower eyelid ectropion in 5 (62.5%), bilateral in 4 (50%); lagophthalmos in 3 (37.5%); chronic blepharitis in 4 (50%). Dry eye affected all patients (100%): mild–moderate in 5 (62.5%), severe in 3 (37.5%), with severe dry eye consistently associated with ectropion. Ocular-surface disease was present in 5 patients (62.5%): chronic conjunctival hyperemia (50%), superficial punctate keratopathy (50%), exposure keratitis (37.5%), and corneal ulceration (12.5%). Corneal complications were more frequent in patients with lagophthalmos (66.7%) than in those without eyelid abnormalities (20%). Visual acuity decrease due to corneal damage occurred in 2 patients (25%); one child was at risk for amblyopia. Six patients (75%) received medical treatment alone; two (25%) underwent surgical correction of ectropion. Intensive lubrication was prescribed for all. Clinical improvement was observed in 7/8 patients (87.5%). Conclusions: Ophthalmic manifestations in ichthyosis are common and can be severe. Eyelid malposition, especially ectropion and lagophthalmos, is the main risk factor for corneal complications. Early ophthalmic assessment, aggressive ocular-surface management, and timely surgical repair of eyelid malposition are essential to preserve vision, particularly in congenital forms.